The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1094/pdis.2001.85.2.231c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the Bemisia tabaci B Biotype in India and an Associated Tomato leaf curl virus Disease Epidemic

Abstract: In May 1999, in the Kolar district of Karnataka State, Bemisia tabaci numbers on tomato increased by approximately 1,000-fold that observed previously (3). This was associated with an epidemic of severe tomato leaf curl disease that caused complete crop failure. DNAs extracted from 35 symptomatic tomato leaf samples collected within the epidemic region all gave the expected 500 to 600 bp amplicon with begomovirus-specific primers A/B (1). These primers amplify from the conserved nonanucleotide TAATATTAC in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…The most likely reason for the similarity of these populations may be the movement of B. tabaci between the countries as a result of human activities. The most recent example of such introduction has been the arrival of the B biotype in India, Pakistan, and China (Banks et al, 2001;Simon et al, 2003;Zhang et al, 2005), and more recently the Q biotype in China (Zhang et al, 2005). The data, which presented here, highlight the real and increasing threat posed by the movement of B. tabaci and potentially new viruses to agriculture in Asia.…”
Section: Discussionmentioning
confidence: 71%
“…The most likely reason for the similarity of these populations may be the movement of B. tabaci between the countries as a result of human activities. The most recent example of such introduction has been the arrival of the B biotype in India, Pakistan, and China (Banks et al, 2001;Simon et al, 2003;Zhang et al, 2005), and more recently the Q biotype in China (Zhang et al, 2005). The data, which presented here, highlight the real and increasing threat posed by the movement of B. tabaci and potentially new viruses to agriculture in Asia.…”
Section: Discussionmentioning
confidence: 71%
“…In another study, Asia1 was found to be predominant in the North of India, butin the South a higher diversity of B. tabaci species was found (ChowdaReddy et al 2012;Ellango et al 2015), whereas in this study Asia II 8 was predominant in the south. A first report of B. tabaci MEAM1 in India was from Banks et al (2001) who collected this invasive species from infected tomato in the Kolar district. Further reports of MEAM1 were primarily from the same region (Rekha et al 2005;Shankarappa et al 2007;Ellango et al 2015) with one find in Dabhoi in the West (Chowda-Reddy et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggested that a differentiation of populations has already occurred, mainly according to the host plant, instead of the geographical region where populations are localized and they had reported that there was no grouping of samples collected on different crops in the same state. Among the biotypes of B. tabaci, the B biotypes, in the previous two decades has been distributed widely and caused tremendous losses world wide as a pest and vector of virus diseases [2,10,30,31] . The B biotype has distinctive biological traits, together with esterase and RAPD patterns that showed little variation [2,7,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Three distinct bands of sizes viz., 350, 800 bp and 1 kb were produced by B11 primer [32] , similar to that in our study clearly distinct bands of 500 bp and 1 kb were produced by the primer OPA 12, while resolved bands were obtained below 500 bp using OPE 04 primer. The B biotype was first recorded in the Kolar district of Karnataka state, South India, during the summer growing season (March-June) of 1999 [30] . In a different study [32] , cluster analyses of RAPD data separated the B. tabaci samples into north and south Karnataka groups.…”
Section: Discussionmentioning
confidence: 99%